The impact of bio-banding on technical-tactical performance in youth handball: first insights from male and female academy players - de la Rubia, A.; García-Sánchez, C.; Andrino, C.; de la Iglesia, C. S.; Ferro, A.; Marquina, M. (Journal of Science and Medicine in Sport, 2026)
Objectives To examine and compare the impact of bio-banding with regard to age group competition on technical-tactical performance in young male and female handball players.